A new statistical thermodynamic mechanism for quantum mechanics - Alpert, Martin (Frontiers in Physics, 2022)
A new quantum mechanics mechanism theory based on statistical mechanics is introduced. This theory is based on corresponding changes in the number of states with associated energy changes at the observer and observed occurring at observer 1) reset and 2) observation. It is shown that a) the change in the number of states has different consequences than determining the “value” obtained at observation, where each state is a possible interaction between the system and the environment. The number of bits, as a measure of information content, is determined in discrete cell size increments. Two experiments are proposed to validate the introduced mechanism. The first experiment is to determine the spatial and temporal characteristics of energy changes and how they are related to the observer and observed during the entire measurement process. The second experiment is designed to determine timing between changes in the number of states in the system at observer reset. It is anticipated that these experiments will demonstrate no time delay, an entangled process, and, hence, explain delayed choice observations. Moreover, they would demonstrate that bits not stored in the system are transferred to the environment at observer reset, so when the number of inputs is greater than the number of outputs, an energy change occurs and interference is observed (wave characteristics). Conversely, if the number of inputs equals the number of outputs, no energy change occurs and no interference is observed (particle characteristics). It is envisioned that upon validating this mechanism theory, it will further the understanding of the measurement process and entanglement’s involvement in that process.